2021
DOI: 10.5194/bg-2020-457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pelagic primary production in the coastal Mediterranean Sea: variability, trends and contribution to basin scale budgets

Abstract: Abstract. We estimated pelagic primary production (PP) in the coastal ( 300 g C m−2) associated with major river discharges, to less productive provinces (

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…While fishing pressure and ocean warming are among the most common drivers of marine communities and play a central role in the Northern Adriatic ecosystem (Barausse et al, 2011, 2014; Blenckner, Llope, et al, 2015; Coll et al, 2010; Fortibuoni et al, 2015, 2017; Lotze et al, 2011), other drivers might explain the changes observed here. Riverine nutrient inputs and a recently decreasing eutrophication level (Barausse et al, 2011; Fortibuoni et al, 2017; Mozetič et al, 2010; Salgado‐Hernanz et al, 2022), changes in lower trophic levels including plankton but also ocean circulation (Conversi et al, 2010), trophic interactions (Barausse et al, 2009; Coll et al, 2009), interactive effect of cumulative drivers (Barausse et al, 2009, 2011; Coll et al, 2009; Fortibuoni et al, 2017), market preferences and other economic factors (Russo et al, 2015) could be relevant drivers of changes. Further analyses, beyond the scope of this paper, will need to be conducted to assess the impact of other drivers on the Northern Adriatic system, possibly based on a combination of modelling approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While fishing pressure and ocean warming are among the most common drivers of marine communities and play a central role in the Northern Adriatic ecosystem (Barausse et al, 2011, 2014; Blenckner, Llope, et al, 2015; Coll et al, 2010; Fortibuoni et al, 2015, 2017; Lotze et al, 2011), other drivers might explain the changes observed here. Riverine nutrient inputs and a recently decreasing eutrophication level (Barausse et al, 2011; Fortibuoni et al, 2017; Mozetič et al, 2010; Salgado‐Hernanz et al, 2022), changes in lower trophic levels including plankton but also ocean circulation (Conversi et al, 2010), trophic interactions (Barausse et al, 2009; Coll et al, 2009), interactive effect of cumulative drivers (Barausse et al, 2009, 2011; Coll et al, 2009; Fortibuoni et al, 2017), market preferences and other economic factors (Russo et al, 2015) could be relevant drivers of changes. Further analyses, beyond the scope of this paper, will need to be conducted to assess the impact of other drivers on the Northern Adriatic system, possibly based on a combination of modelling approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the hypothesis represented by our model is that changes in SST can modify the relationship between fishing pressure and the community status from linear to discontinuous, making regime shifts possible and creating the potential for hysteresis. This could happen, for example, because the ongoing sea warming could affect ecosystem functioning by reducing system productivity (see for example Salgado‐Hernanz et al, 2022), and thus smaller changes in fishing pressure could have comparatively large ecosystem‐wide consequences. Of course this is just an example and temperature can influence marine ecosystem functioning in many ways, for example by affecting species growth, food consumption rates or spatial distribution.…”
Section: Methodsmentioning
confidence: 99%
“…However, while this effect is evidenced in shallow nearshore waters, its influence in the ocean is estimated to be minimal (Wang et al, 2018). In the Mediterranean Sea, high coast population growth rates and concomitant food demand have resulted in dramatic increase of water demand for irrigation farming and fertilizer use (Ryan, 2008). Indeed, while the freshwater discharge of Mediterranean rivers has significantly reduced during recent decades (~20%), the corresponding total nitrogen inputs to coastal seas are estimated to have increased by a factor up to 5, fuelling PP in river influenced areas (Ludwig et al, 2009).…”
Section: Long-term Variability and Trendsmentioning
confidence: 99%
“…Coastal ocean waters (i.e., < 200 m depth) are an important link between the land and the open ocean. They act as a buffer between terrestrial and human influences and the open ocean (Liu et al, 2000). Despite their relatively reduced extension (~7% of ocean surface area; Gattuso et al, 1998), they behold some of the most productive habitats on the planet.…”
Section: Introductionmentioning
confidence: 99%
“…Most coastal studies have a focus on specific regions and/or times (Estrada, 1996;Marty et al, 2002;Moutin and Raimbault, 2002;Rahav et al, 2013). Observed rates of climate change in the Mediterranean basin exceed global trends (Cramer et al, 2018) and future warming in the Mediterranean region is expected to be above global rates by 25 % (Lionello and Scarascia, 2018).…”
Section: Introductionmentioning
confidence: 99%